LOCAL INFORMATIONAL SYSTEM IN DEPARTMENTS TSZL OF HARWARE PLANT - V. V. Medvedev; A. S. Baranovskij (Литьë и металлургия)
Benefit of implementation of Laboratory informational system in hardware casthouses of RUP «BMZ» is shown.